Modals, Pronouns and Complement Clauses. - Hernández, Nuria (Topics in English Linguistics TiEL ;, 2011)
This is the second volume of the multi-volume set A Contemporary Grammar of British English Dialects. The book again offers qualitative as well as corpus-based quantitative studies on grammatical variation in the British Isles. The three parts investigate complement clauses (Daniela Kolbe), personal pronouns (Nuria Hernández) and modals (Monika Edith Schulz). The volume is of interest to dialectologists, sociolinguists, typologists, historical linguists, grammarians, and anyone working on the structure of spontaneous spoken English.